Distribution of fish in tributaries of the lower Taieri/Waipori rivers, South Island, New Zealand - Bruno O. David; Gerard P. Closs; Chris J. Arbuckle (New Zealand Journal of Marine and Freshwater Research, 2002)
The distribution of fish within eight small streams feeding into the lower Taieri and Waipori Rivers on the east coast of New Zealand's South Island was examined. A total of eight native and two introduced species were recorded. Eels ( Anguilla spp.) and giant kokopu ( Galaxias argenteus Gmelin) were the most widely distributed species being located in all streams surveyed. Common bullies ( Gobiomorphus cotidianus McDowall) and brown trout ( Salmo trutta Linnaeus) were also widely distributed being detected in seven and six of the streams respectively. Three streams of potential conservation significance were identified. These were Picnic Gully Creek which contained a significant population of banded kokopu ( Galaxias fasciatus Gray), a Category C threatened species, and Cullens and Alex Creeks which contained significant populations of giant kokopu, a Category B threatened species. The population of giant kokopu in Cullens and Alex Creeks currently represents the largest known population of this species on the east coast of New Zealand (excluding Southland). It has been suggested that brown trout may influence the distribution of native galaxiids. The longitudinal distribution of giant kokopu and brown trout in streams was examined at night using a continuous spotlight sampling approach. Distributions of these two species rarely overlapped at a local scale. Coarse habitat use data indicated that brown trout regularly occupied a variety of habitat types including modified agricultural channels. In contrast, giant kokopu rarely used agricultural channels being predominantly located in pool habitats.

Absolute geostrophic currents in the East Auckland Current region - P. J. H. Sutton; T. K. Chereskin (New Zealand Journal of Marine and Freshwater Research, 2002)
Absolute geostrophic currents are estimated for the full depth of the water column off the north‐east coast of New Zealand for February 1998. This is achieved by objectively‐mapping subsurface Acoustic Doppler Current Profiler (ADCP) data using horizontal length scales determined from repeat high‐resolution Expendable Bathythermograph (XBT) data and enforcing horizontal non‐divergence. The resulting 2‐dimensional map of velocity at a single depth is used as a level of known motion. Velocities at all other depths are calculated by combining this known motion with the geostrophic shear calculated from hydrographic measurements. The flow field exhibits the expected large‐scale features: the East Auckland Current (EAUC) and the North Cape Eddy. It also indicates that these flows were underestimated by the standard use of a 2000 m level of no motion, i.e., these features penetrate 2000 m. Flows at 2000 m are found to be as large as 30–40 cm/s with a mean of 17 cm/s. This is less than the maximum flows measured by deep current meters, but significantly higher than the mean. Comparisons of the ADCP‐referenced surface flow field with the surface flow field calculated by combining climatology and TOPEX/Poseidon sea‐surface height (SSH) show general qualitative agreement. The two independent flow estimates are similar in the core of the EAUC, with the differences being c. 10 cm/s, whereas the agreement further offshore is not as good.

Thermal marking of rainbow trout ( Oncorhynchus mykiss ) otoliths - Bryan Van Der Walt; Robert A. Faragher (New Zealand Journal of Marine and Freshwater Research, 2002)
A small‐scale experiment was done to test the feasibility of thermally marking hatchery‐reared rainbow trout ( Oncorhynchus mykiss Walbaum) fry that are released into rivers and impoundments in New South Wales (NSW), Australia. Fry of rainbow trout were exposed to two different 48‐h thermal cycles each of a cold and warm water period. One thermal regime consisted of a cold water period during which the temperature was reduced from 14 to 8°C for 18 h followed by a return to 14°C for 30 h. For the second thermal treatment, water temperature was reduced to 4°C for 10 h followed by a period of 38 h at 14°C. Thermal cycles were repeated 4 and 8 times for each thermal regime, respectively. Following a growth period after treatment, obvious marks were visible on all treated otoliths as distinct from control otoliths. The 10°C differential treatment created the most visible patterns and growth of these fish was not significantly different from control fish. This marking method could be applied to normal hatchery practices to evaluate the effectiveness of large‐scale rainbow trout stockings in NSW.

First encounter with a live male blanket octopus: The world's most sexually size‐dimorphic large animal - M. D. Norman; D. Paul; J. Finn; T. Tregenza (New Zealand Journal of Marine and Freshwater Research, 2002)
The first encounter with a live male blanket octopus, Tremoctopus violaceus Chiaie, 1830, illustrates the most extreme example of sexual size‐dimorphism in a non‐microscopic animal. Females attain sizes of up to 2 m long—almost 2 orders of magnitude larger than the 2.4‐cm‐long male. Weight ratios between the sexes are at least 10 000:1 and are likely to reach 40 000:1. Sexual selection and the unique defensive strategy of carrying cnidarian stinging tentacles may both have contributed to the evolution of this extreme size‐dimorphism. Such dimorphism is not seen in any other animal remotely as large.

Lipid content in rainbow trout ( Oncorhynchus mykiss ) fry and parr reared in spawning tributaries of Lake Taupo, New Zealand - Michel Dedual (New Zealand Journal of Marine and Freshwater Research, 2002)
The total lipid content of fry (25–30 mm) and parr (55–110 mm) of rainbow trout ( Oncorhynchus mykiss Richardson 1836) was measured in spring 1996 and 1997 and in autumn 1997 in six trout‐rearing tributaries of Lake Taupo, New Zealand. The fat content of fry was variable between streams and some streams had a higher inter‐annual variation than others. The fat content of parr was also variable among streams but no difference could be found between seasons. The streams that produced fry with high fat content did not always produce parr with high fat content.

Ecoregional differences in macrophyte and macroinvertebrate communities between Westland and Waikato: Are all New Zealand lowland streams the same? - I. C. Duggan; K. J. Collier; P. D. Champion; G. F. Croker; R. J. Davies‐Colley; P. W. Lambert; J. W. Nagels; R. J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2002)
We characterised water chemistry, aquatic habitat, macrophytes, and invertebrate assemblages in eight lowland streams—five in Westland, South Island, and three in the Waikato, North Island, New Zealand. Factors influencing invertebrate community structure over large (between ecoregions) and small (within an ecoregion) spatial scales were investigated. The Westland sites had generally lower nutrient concentrations, conductivity, and water clarity, and coarser substrates than the Waikato sites, reflecting differences in geological history, hydrology, and land‐use intensity. The macrophyte communities in each region were very different in species composition and structure, but seasonal abundance patterns in both regions were fairly typical of New Zealand streams in general. Alien obligate submerged macrophyte species were absent from the Westland lowland stream sites, and may partly reflect the isolated nature of this region where colonisation by asexual macrophytes would be difficult. Waikato stream invertebrate faunas were dominated by molluscs (mainly Potamopyrgus ) and crustaceans (mainly amphipods), whereas Epheme‐roptera, Trichoptera, and Coleoptera taxa dominated the Westland stream faunas. The overall structure of invertebrate assemblages appeared to be influenced by a combination of regional differences in substrate type, nutrient concentrations, water clarity, and macrophyte cover. Westland streams with more upstream pastoral development had higher proportions of molluscs than those with predominantly forested or scrub catchments. Our study suggests that large‐scale ecoregional differences may override smaller‐scale land‐use effects on lowland stream invertebrate communities, and that management strategies should be developed on an ecoregional basis for lowland stream ecosystems.

Fish effects on charophyte establishment in a shallow, eutrophic New Zealand lake - Mary D. De Winton; Aleki T. Taumoepeau; John S. Clayton (New Zealand Journal of Marine and Freshwater Research, 2002)
Fish exclosures were deployed within shallow, eutrophic Lake Rotoroa, Hamilton, New Zealand to assess the influence of an alien‐dominated fish population on establishment by charophytes. Replicated mesh exclosures were placed at sites differing in wave exposure and received transplanted charophyte oospores and plants, with identical material placed outside. Charophyte establishment from oospores and plant biomass were greater inside exclosures compared with outside. Wave exposure did not depress germling response and the effect of fish exclosures on charophyte establishment was least apparent at the most exposed site. Exclosures did not have a statistically significant influence on the light climate, and epiphytic algal development was similar or higher inside the exclosures. However, sediment mobilisation was lower inside the exclosures. Results suggest that fish were primarily responsible for the poor performance of unprotected charophytes in Lake Rotoroa, with fish effects on plants operating via direct disturbance or grazing.

Nutrient cycling and fluxes in Beatrix Bay, Pelorus Sound, New Zealand - M. Gibbs; A. Ross; M. Downes (New Zealand Journal of Marine and Freshwater Research, 2002)
Nitrogen (N) and light availability limit phytoplankton growth and hence regulate food supply for mussel farming in Pelorus Sound, New Zealand. In Beatrix Bay, a large 35‐m deep embayment off Pelorus Sound, the supply of N is heavily influenced by physical factors. Bottom intrusions of N‐rich or depleted oceanic water occur in the main channel of Pelorus Sound and N‐depleted, phytoplankton‐enriched Pelorus River water characterises the near‐surface low salinity field. Inside Beatrix Bay, nutrient cycling via phytoplankton uptake, sedimentation, and subsequent regeneration from the sediments by mineralisation, also has an important influence on the availability of N in the water column. However, almost continuous salinity or thermally induced density stratification, or both, within Beatrix Bay meant that the upper and lower water columns were often decoupled so that N regenerated from the sediments was not readily available in the upper water column, and phytoplankton settling from the upper water column may not reach the sediments directly below because of large horizontal transport. The N supply in the upper water column of Beatrix Bay, where the mussels are farmed, is most likely regulated by advection in and out of the bay from external sources. Conversely, the N concentrations below the pycnocline could be almost entirely supplied via mineralisation from the sediments. The rates of sediment N regeneration were seasonally dependent. During winter, when sedimentation exceeds mineralisation, N accumulates in the sediments at a rate of up to 10 mg m –2 day –1 , whereas in summer, when mineralisation exceeds sedimenation, N is lost from the sediments at rates of up to 9 mg m –2 day –1 .

Fish assemblages in the Hauraki Gulf, New Zealand - Terese H. Kendrick; Malcolm P. Francis (New Zealand Journal of Marine and Freshwater Research, 2002)
Species assemblages in the Hauraki Gulf, New Zealand, and the factors affecting them, were determined from abundance data collected from 1381 trawl tows by two research vessels during 1964–97. Correspondence Analysis and Ward's Cluster Analysis were used to identify assemblages, and Canonical Correspondence Analysis (CCA) to explore the relationships between the assemblages and depth, sediment type, latitude, longitude, and year. Twenty‐six species that occurred in more than 5% of the stations were assigned to four assemblages, and a further four species showed no affinities with other species. For four commercial species, there was no evidence of ontogenetic variation in assemblage membership. The CCA models explained only 11–12% of the variance in the data. Year was the most important explanatory variable, suggesting that between‐year variation in species abundance affected assemblage composition. Sediment type was also important for many species. Assemblage A species were most abundant at shallow ( 50 m) mud sites, and Assemblage D species at deep mud sites. Assemblage C species had varied habitat preferences. The commercially important Pagrus auratus and Nemadactylus macropterus preferred mud, and Chelidonichthys kumu preferred sand. Zeus faber was most abundant at muddy sites, but also occurred (sometimes abundantly) at sandy sites.

Identification of galaxiid nests, emigrating larvae and whitebait, using mitochondrial DNA control region sequences - Sjaan C. Charteris; Peter A. Ritchie (New Zealand Journal of Marine and Freshwater Research, 2002)
We used mitochondrial (mt) DNA sequences to identify nests, emigrating larvae, and whitebait of three species of diadromous galaxiids, collected from eight locations in Taranaki and Manawatu, New Zealand. DNA was extracted from whole larvae and fin clips, and a 416 base pair (bp) sequence of mtDNA control region was determined. Four Galaxias fasciatus Gray (banded kokopu) and 12 G. postvectis Clarke (shortjaw kokopu) nests were identified. Galaxias postvectis, G. fasciatus , and G. brevipinnis Günther (koaro) individuals were detected migrating downstream from drift samples collected between May and June 2001. Furthermore, we identified three species from samples of whitebait revealing three G. postvectis , six G. fasciatus , and three G. brevipinnis . Species of larval eggs, larvae, and whitebait can be accurately identified by molecular methods. These methods provide an opportunity to help in the understanding of nest habitat choice, hatching time, migration, and choice of rivers by whitebait species.

Cricotopus and Paratrichocladius ( Chironomidae : Insecta) in New Zealand, with description of C. hollyfordensis n. sp., and redescriptions of adult and immature stages of C. zealandicus and P. pluriserialis - I. K. G. Boothroyd (New Zealand Journal of Marine and Freshwater Research, 2002)
Cricotopus van der Wulp and Paratrichocladius Santos Abreu are among the most common genera of Chironomidae found in fresh waters throughout New Zealand. Imago, pupa, and fourth (final) instar larva of Cricotopus hollyfordensis n. sp. are described, and the male imagines, pupae, and larvae of Cricotopus zealandicus Hutton and Para‐trichocladius pluriserialis Freeman are redescribed from new material. C. hollyfordensis n. sp. can be distinguished from other Cricotopus species by antennal ratio and absence of tibial and abdominal markings in the male imago; shape and form of the thoracic horn, distinctive abdominal spinule patterns and lateral setae in the pupa; and mentum and mandible characteristics in the larvae. The combination of tibial and abdominal markings of the male imago; thoracic horn and abdominal spinule patterns of the pupa; and mentum and mandible characteristics of the larva distinguish C. zealandicus from P. pluriserialis and all other New Zealand Cricotopus species. P. pluriserialis is distinguished from Cricotopus species by the presence of normal and erect dorsocentral setae in the adult; smooth thoracic horn and distinctive abdominal spinule patterns of the pupa; mentum and mandible characteristics, supra‐anal setae longer than 2–3 abdominal segment lengths, and abdominal setae simple, never in tufts, in the larva. C. hollyfordensis n. sp. has been recorded from a fast flowing mountain

Influence of large woody debris on channel morphology in native forest and pine plantation streams in the Nelson region, New Zealand - Brenda R. Baillie; Tim R. Davies (New Zealand Journal of Marine and Freshwater Research, 2002)
The influence of large woody debris (LWD) on channel morphology was assessed in five pine plantation and five native forest streams in the Nelson region of New Zealand. LWD volumes averaged 127 m 3 ha –1 in pine plantation streams and 94 m 3 ha –1 in native forest streams. Most of the LWD in pine and native streams had no influence on channel morphology (78 and 54%, respectively). Those LWD pieces influencing channel morphology contributed mainly to sediment storage in both pine and native streams as well as flow deflection and debris collection in the native streams. Wood aligned either perpendicular or obliquely to stream flow and positioned on or partly buried in the stream bed had the greatest influence on channel morphology. There were twice as many pools in native streams as in pine streams, and scour processes formed the majority of pools. LWD influenced c. 50% of pool formation in both pine and native streams and increased pool variety. LWD volumes in these streams are low compared with Pacific north‐west streams of the United States, similar to streams in the subalpine forest of Colorado, and higher than volumes in the more modified streams of Europe. Similarities in pool forming processes, pool type, and spatial arrangement of wood influencing channel morphology are apparent between the streams in this study and streams of the Pacific north‐west and Colorado.

First record of a wild population of the tropical snail Melanoides tuberculata in New Zealand natural waters - I. C. Duggan (New Zealand Journal of Marine and Freshwater Research, 2002)
The thiarid snail Melanoides tuberculata (Müller, 1774), native to the Middle East and East Africa, is recorded from the wild in New Zealand for the first time from a geothermally influenced stream at Golden Springs, near Taupo. Introduction was most likely the result of one or more releases from tropical aquaria, although the timing of release is uncertain. Specimens were collected at temperatures of 29.0 and 30.4°C, and survival at these sites is likely dependent on the elevated stream temperatures. The possible spread of this species to other habitats, and potential effects on native thermal water communities, are discussed.

Genetic and meristic variation in black and smooth oreos in the New Zealand exclusive economic zone - P. J. Smith; P. J. McMillan; B. Bull; S. M. McVeagh; P. M. Gaffney; S. Chow (New Zealand Journal of Marine and Freshwater Research, 2002)
Meristic and genetic methods were used to determine the stock relationships of black Allocytus niger (James, Inada & Nakamura, 1988) and smooth oreo Pseudocyttus maculatus (Gilchrist, 1906) in the New Zealand Exclusive Economic Zone (EEZ). Samples were collected from four management areas—OEO 1 (south‐west), OEO 3A (Chatham Rise west), OEO 4 (Chatham Rise east), and OEO 6 (subantarctic) during the 1998 October‐December spawning period. Lateral line scale counts and pyloric caeca counts revealed differences between black oreo samples from OEO 6 and the other three OEO management areas. Lateral line scale counts in smooth oreo showed no significant differences between areas. Genetic analyses of four non‐coding regions of nuclear DNA and mitochondrial (mt) DNA haplotypes in black oreo showed no significant differentiation among the four management areas. Likewise for smooth oreo, genetic analyses of five non‐coding regions of nuclear DNA and mtDNA haplotypes showed no overall regional differentiation, although there was weak evidence at one locus for a difference between OEO 3A and OEO 6. The data do not reject the null hypothesis of a single genetic stock in New Zealand waters, and are typical of marine species with long pelagic juvenile stages.

Growth and population dynamics of crayfish Paranephrops planifrons in streams within native forest and pastoral land uses - Stephanie M. Parkyn; Kevin J. Collier; Brendan J. Hicks (New Zealand Journal of Marine and Freshwater Research, 2002)
Population dynamics of crayfish ( Paranephrops planifrons White) in streams draining native forest and pastoral catchments, Waikato, New Zealand, were investigated from September 1996 to July 1998. Crayfish densities were generally greater in native forest streams because of high recruitment over summer, but varied greatly between streams in both land uses. Peak densities in summer were 9 crayfish m ‐2 in native forest and 6 crayfish m ‐2 in pasture streams, but peak biomass in summer was much greater in pasture streams. Mark‐recapture data showed that crayfish, particularly juveniles, in pasture streams grew faster than in native forest streams, through both greater moult frequency and larger moult increments. Females reached reproductive size at c. 20 mm orbit‐carapace length (OCL) after their first year in pasture streams, but after 2 years in native forest streams. Annual degree days >10°C appeared to explain the differences in the timing of life cycles. Estimates of annual crayfish production (range = 0.8–3.4 g dry weight m ‐2 year –1 ) were similar in both land uses, and P/B ratios were between 0.95 and 1.2. Despite deforestation and conversion to pasture, crayfish in these Waikato hill‐country streams have maintained similar levels of annual production to those in native forest streams, although juvenile growth rates have increased and longevity has decreased.

Reproductive output of Crepidula fecunda females: Distribution of energy in the production of gametes and capsular walls - O. R. Chaparro; M. L. Flores (New Zealand Journal of Marine and Freshwater Research, 2002)
A study was undertaken on the distribution of energy in the reproductive output of Crepidula fecunda Gallardo 1979, a species which provides parental care of deposited eggs during their incubation period. A positive relationship was observed between the shell dimensions and dry tissue weight of the females which was not in turn related to the number of capsules incubated, nor with the size or dry weight of eggs deposited. Positive relationships were observed, however, between the female size and the capsular size and with the numbers of eggs per capsule and per spawning. No significant relationship was observed between the size of the females and the biochemical compositions of the individual eggs, but there was a positive relation between the sizes of the females and the total content of proteins, carbohydrates, and lipids deposited in each capsule wall and in all of the eggs of each spawning. The energetic cost per embryo varied from 0.045 to 0.049 J/embryo in females from 0.5 to 3.5 g tissue dry weight, respectively. Of the total energy invested per spawning, between 92 and 98% was in the eggs, and 2–8% in the capsular walls. Thus, parental care was relevant to the distribution of energy in the reproductive output, favouring production of gametes rather than of protective structures such as capsular walls.

Reproduction of the sea urchin Evechinus chloroticus (Echinodermata: Echinoidea) in a New Zealand fiord - Miles D. Lamare; Paul E. Brewin; Mike F. Barker; Stephen R. Wing (New Zealand Journal of Marine and Freshwater Research, 2002)
The reproductive cycle of Evechinus chloroticus (Val.) was examined at three (outer, mid, and inner) sites in Doubtful Sound, Fiordland over a 3‐year period. We found that sea urchins from all three populations had an annual gametogenic cycle, the timing of which was temporally and spatially consistent. Inter‐individual variation in the gametogenic cycle was noted within each population, however, initiation of gametogenesis was generally synchronous among males and females and among sites, occurring in May/June. Strong asynchrony in gamete maturation was observed in Deep Cove, occurring in males 4–5 months earlier than females. Spawning occurred in December at the inner and mid fiord sites, while occurring in January at the outer fiord site. Reproductive potential (maximum gonad index) and output (weight of gametes released/g of animal/year) varied spatially and temporally, where there was a consistent decreasing trend in reproductive potential and output with increasing distance away from the fiord entrance. Spatial variation in reproductive output may be associated, in part, with the strong ecological gradient found in Doubtful Sound, where there is a reported decrease in macrophyte biomass and cover towards the fiord headwaters. The implications of spatial differences in gonad production with respect to the population biology and fisheries management of E. chloroticus in the fiords are discussed.

Occurrence and use of Compsopogon coeruleus (Rhodophyta: Compsopogonaceae) in Fiji, South Pacific - G. Robin South; Posa A. Skelton (New Zealand Journal of Marine and Freshwater Research, 2002)
The rhodophyte Compsopogon coeruleus (Balbis ex C. Agardh) Montagne is newly recorded from Fiji, South Pacific. Plants occur in dense masses in the Wainivesi River in the province of Tailevu. Local villagers collect the plants and use them to cook a “pudding” with tinned fish, very similar to “puddings” prepared by coastal Fijians using marine species such as Gracilaria and Hypnea . This is the first documented account of the use of Compsopogon as a gelling agent in the preparation of human food.

Composition and flight periodicity of adult caddisflies in New Zealand hill‐country catchments of contrasting land use - Brian J. Smith; Kevin J. Collier; N. Jane Halliday (New Zealand Journal of Marine and Freshwater Research, 2002)
A total of 6085 adult Trichoptera (excluding Hydroptilidae) representing 12 families, 31 genera, and 56 species were collected by a combination of Malaise net and light trapping from July 1998 to July 1999 at three hill‐country sites of contrasting catchment land use (100% native forest, a pasture site with native forest headwaters, and 100% pasture) in the Waikato, northern New Zealand. Forty‐eight species of Trichoptera were collected from Malaise nets and 45 species from light traps. Eleven species of Trichoptera were only ever collected from the Malaise nets and seven species from only the light traps. At the native forest site, Malaise nets collected more species and taxa of conservation interest than did light traps, possibly reflecting diurnal activity or non‐attraction to light by some species. Several species of Trichoptera showed site specificity and most of these were found at the native forest site. Twenty‐eight species were active for at least 6 months of the year with at least four species active all year. A minimum overnight air temperature of at least 9°C was required to induce Trichoptera flight activity, but large‐scale flight activity may require temperatures greater than 14°C. Trichoptera with free‐living and net spinning larvae exhibited extended flight periods, and for three species examined there were bi‐modal activity peaks. Adult caddisflies with cased larvae which grazed on epilithic food resources generally had reduced flight periods and one species had a well‐defined, synchronous periodicity. These findings suggest flight periodicity may partly be a functional response to larval food availability.

Variability in spatial and temporal abundance of glass eels (Anguilla spp.) in New Zealand waterways - D. J. Jellyman; B. L. Chisnall; J. R. E. Sykes; M. L. Bonnett (New Zealand Journal of Marine and Freshwater Research, 2002)
The regional and annual variability in the abundance of newly arrived glass eels, Anguilla australis (Richardson) and Anguilla dieffenbachii (Gray), were examined using glass eel densities (n = 100 m –2 ) from electric‐fishing samples collected at 14‐day intervals over 5 years from 13 streams/ rivers throughout New Zealand. Although the density of shortfin eels exceeded that of longfin eels for any one year, the annual trends for both species were generally similar. Both species behaved independently, but significant factors affecting density were “year” and “region”, with the pronounced regional effect for longfin eels attributed to “coast” (east or west), but not “island” (north or south). There was no evidence of declining recruitment for longfin glass eels.

Distribution, seasonality, lengths, and feeding behaviour of whale sharks (Rhincodon typus) observed in New Zealand waters - C. A. J. Duffy (New Zealand Journal of Marine and Freshwater Research, 2002)
Data from 36 whale shark (Rhincodon typus Smith, 1828) sightings off north‐east North Island, New Zealand are summarised. Sightings were concentrated over the outer shelf and shelf break in areas influenced by the East Auckland Current at sea surface temperatures (SST) of 21–24°C. Sightings occurred from late spring to early autumn (November‐April) but were most frequent in midsummer (February) when upwelling along the north‐east shelf is weakest. The data indicate whale sharks occur off north‐east New Zealand most summers, including those when SST is colder than usual. A cluster of sightings and three observations of whale sharks feeding on schools of anchovy (Engraulis australis) near Whale Island, Bay of Plenty, suggest whale sharks may aggregate seasonally in this area. Estimated total lengths (TL) of 26 whale sharks ranged from 3.5 to 15 m, with 73% between 6 and 9 m TL.

Habitat use by juvenile lampreys (Geotria australis) in a large New Zealand river - D. J. Jellyman; G. J. Glova (New Zealand Journal of Marine and Freshwater Research, 2002)
Ammocoetes (larvae) of Geotria australis Gray, were sampled in a large South Island, New Zealand, river during summer to determine their distribution and habitat associations. Ammocoetes were widely distributed along the length of the river, being present at 66 of the 95 sites sampled. They ranged in density from 0 to 180 m –2 , and were associated with habitat type (mainly runs), overhead shade, and substrate features (depth or the proportion of fine sand). The amount of particulate organic matter was negatively correlated with ammocoete abundance.

Temporal and spatial quantification of aquatic invertebrate drift in the Maruia River, South Island, New Zealand - Karen A. Shearer; John W. Hayes; John D. Stark (New Zealand Journal of Marine and Freshwater Research, 2002)
We investigated temporal (day‐to‐day and season) and spatial (reach) variability of drift with the aim of guiding sampling protocol for quantifying drift at the whole river or reach scale. Overall, we found aquatic drift density and biomass varied considerably seasonally (CV = 72.9, 88.1) and to a lesser extent spatially (CV = 31.3, 30.7) and from day‐to‐day (CV = 45.2, 39.4). Although spatial and day‐to‐day variation in drift density and biomass were similar, sampling logistics suggest spatial sampling would be more cost‐effective and less time consuming. Drift density and biomass estimated from top samplers was often higher than estimates from samplers near the streambed or mid‐water column. A reliable estimate of mean densities and biomass at a site may require only two samplers— a top sampler and either a middle or bottom sampler. In our study, we calculated that sampling at four sites over 1 or 4 days at one site would be required to obtain a 95% CI within 50% of the mean drift density. Eight sites over 1 or 10 days at one site would be required to achieve a 95% CI within 25% of the mean drift density.

Photo‐identification of short‐beaked common dolphins (Delphinus delphis) in north‐east New Zealand: A photo‐catalogue of recognisable individuals - Dirk R. Neumann; Alexandra Leitenberger; Mark B. Orams (New Zealand Journal of Marine and Freshwater Research, 2002)
Photo‐identification has been established as a helpful tool in cetacean research. However, no study to date has attempted to apply this method to short‐beaked common dolphins (Delphinus delphis L.). We present here the results of two studies that were conducted concurrently in Mercury Bay and the Hauraki Gulf on the north‐east coast of New Zealand's North Island. Methods for distinguishing between individual dolphins are discussed. Sighting records of recognisable individuals indicate that some common dolphins move between Mercury Bay and the Hauraki Gulf (100 km distance), as well as between Mercury Bay and Whakatane (200 km distance). Common dolphin abundance and site fidelity appeared to be greater in the Hauraki Gulf than in Mercury Bay. A selection of photographs of distinct individuals is presented to allow future studies to compare their sighting records to ours, which may help establish the extent of home ranges, site fidelity, and possibly even longevity for common dolphins.

Abundance, distribution, and size structure of toheroa (Paphies ventricosa) at Ripiro Beach, Dargaville, Northland, New Zealand - Johyphen; Anne M. Akroyd; Kim A. R. Walshe; Russell B. Millar (New Zealand Journal of Marine and Freshwater Research, 2002)
The distribution of toheroa (Paphies ventricosa Gray) beds, and the abundance and size structure of toheroa at Ripiro Beach, Dargaville, New Zealand, were determined by a two‐phase stratified sample survey. The first phase was undertaken in February and March 1999 and the second phase in June 1999. The first phase located and sized 45 toheroa beds, and stratified the beds according to the observed density of siphon holes. A total of 53 transects were sampled. The transects were run perpendicular to the shoreline and positioned systematically within each stratum. Along each transect the sampling of beds was done at 5 m intervals using a 1 × 0.5 m quadrat. Outside of the beds, sampling was done at 10 m intervals. The total number of toheroa 75 mm (previous minimum legal size) was estimated to be 3.3 million with a standard error of 480 000. This abundance of legal‐sized toheroa is roughly comparable with numbers last seen at Ripiro Beach in the late 1960s. The total abundance of toheroa of all sizes was estimated to be 113.5 million with a standard error of 33 million. It appears that there has been good recruitment of + toheroa on Ripiro Beach and the abundance of toheroa of all size ranges has greatly increased since the previous survey in 1974.

Reproductive biology and population structure of the banded wrasse, Notolabrus fucicola (Labridae) around Kaikoura, New Zealand - Christopher M. Denny; David R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2002)
Notolabrus fucicola Richardson, a large common labrid inhabiting rocky reefs around New Zealand and southern Australia, were collected monthly from December 1996 to February 1998 around Kaikoura, New Zealand. They were found to be asynchronous spawners and followed the typical labrid spring‐summer seasonal pattern of reproduction from July to December. Compared with other New Zealand labrids that are protogynous hermaphrodites, N. fucicola was found to be a secondary gonochorist, where individuals change sex before maturation. It is a dichromatic species but not sexually dimorphic. It is also monandric where only one morphological male type is present. Despite finding no transitional gonads, it is still possible that particular environmental or social conditions could induce sex change in at least a small proportion of fishes.

Density effects on juvenile shortfinned eel (Anguilla australis) cover preferences in replicate channels - G. J. Glova (New Zealand Journal of Marine and Freshwater Research, 2002)
The effects of density on day‐time cover preferences of juvenile (100–199 mm total length) shortfinned eels (Anguilla australis Richardson) were tested in replicate channels provided with natural (cobbles, macrophytes, woody debris) and artificial (shade, plastic pipes) cover during summer. The densities used were 10, 20, 30, 40, 50, 60, 80, 100, and 200 eels channel –1 (each channel = 2.4 m 2 ), with each density tested in triplicate, or better. Eels used cobbles and macrophytes almost exclusively, with cobbles being the most preferred and their use increased with increasing density; however, at 200 eels channel –1 , escape behaviour was evident during the night. In tests at 100 eels channel –1 , with only woody debris, plastic pipes, and shade sections available, the eels occupied woody debris, pipes, and shade in decreasing order. In further tests at 100 eels channel –1 , with cobbles, macrophytes and woody debris included, but with plastic pipes partially buried in the substrate and shade sections lowered to within 20 mm of the bottom, still only cobbles and macrophytes were used. Finally, in tests of 10, 50, and 100 eels channel –1 , with cover in each channel consisting of cobbles, macrophytes, woody debris, fallen sod (clumps of natural stream bank with riparian grasses), and modified shade (i.e., lowered to within 20 mm of the bottom with macrophyte rootlets attached to underside), eels preferred cobbles, shade, and fallen sod in decreasing order at all three densities. Overall, the findings of this study do not lend strong support to the hypothesis that juvenile eels use a greater variety of cover with increasing population density.

Effect of substrate stability and canopy cover on stream invertebrate communities - Erna M. Zimmermann; Russell G. Death (New Zealand Journal of Marine and Freshwater Research, 2002)
Disturbance can be an important determinant of stream benthic invertebrate community structure. Whether this is a result of the direct loss of invertebrates, an alteration to the food base of the community by the disturbance, or a combination of both, is never clear. We examined this question by conducting a disturbance experiment under artificial cover where low light limited periphyton growth and minimised the effect of disturbance on periphyton abundance. The experiment was conducted using baskets of natural substrate in a spring‐fed Taranaki Ring Plain stream, Taranaki, New Zealand during February and March 2000. Baskets were placed in the open or under cover and half were disturbed every week for 4 weeks. The artificial cover dramatically reduced periphyton biomass. Presence or absence of cover was the primary determinant of what invertebrate taxa dominated in the baskets, most likely as a result of differences in food resources. The filter feeding Coloburiscus humeralis dominated numerically in the covered baskets, whereas the generalist grazers Deleatidium spp., Beraeoptera roria , Orthocladiinae, and Diamesinae dominated numerically in the open baskets. However, cover had no effect on the overall abundance and species richness of the experimental baskets but disturbance reduced abundance and to a lesser extent species richness.

Influence of hydrologic exchange patterns on water chemistry and hyporheic invertebrate communities in three gravel‐bed rivers - Reece T. Fowler; Mike R. Scarsbrook (New Zealand Journal of Marine and Freshwater Research, 2002)
The influence of hydraulic exchange patterns on hyporheic water chemistry and invertebrate community composition was measured in three gravel‐bed rivers of southern Hawke's Bay, North Island, New Zealand. Based on patterns reported overseas we predict that down‐welling waters will be similar to surface waters in chemical characteristics and epigean animals will be more common in down‐welling waters than in up‐wellings, which would have a different chemical signature to the surface waters and a fauna dominated by hypogean invertebrates. Conductivity, pH, and temperature of hyporheic water were least like those of surface waters at up‐wellings in the groundwater‐fed Makaretu River. Only 6% of the invertebrate fauna of these up‐wellings comprised epigean animals. In contrast, in the groundwater‐recharging Tukituki and Waipawa Rivers, hyporheic water chemistry was similar to that of surface water in down‐wellings and 40% of the community comprised epigean animals by abundance. Significant increases (P 0.05) in species diversity and taxonomic richness was also identified in down‐welling zones compared with up‐wellings. Species diversity and taxonomic richness were lowest in up‐wellings in the Makaretu where hypogean animals dominated the hyporheic fauna. Species diversity and taxonomic richness were higher in down‐wellings than up‐wellings because more epigean taxa were present.

Population genetic structures of two New Zealand stream insects: Archichauliodes diversus (Megaloptera) and Coloburiscus humeralis (Ephemeroptera) - Ian D. Hogg; Pia Willmann‐Huerner; Mark I. Stevens (New Zealand Journal of Marine and Freshwater Research, 2002)
We examined the population genetic structure (allozyme variation) of two New Zealand aquatic insects: Archichauliodes diversus (Walker) (Megaloptera) and Coloburiscus humeralis (Walker) (Ephemeroptera); and tested the hypothesis that species with limited adult dispersal abilities would show high levels of genetic differentiation among hydrologically isolated habitats. Both species were characterised by low levels of within‐population genetic variability (e.g., H exp = 0.06 and 0.04 for A. diversus and C. humeralis , respectively). However, genetic differentiation among sites was considerably greater for A. diversus relative to C. humeralis (F ST = 0.57 and 0.03, respectively). A. diversus consisted of two genetically distinct groups in the North Island ( I = 0.96), and a third group from the South Island ( I = 0.67). By contrast, allelic differences among C . humeralis were minimal ( I > 0.99, in all cases), and appeared unrelated to geographic proximity or habitat type. We suggest that a combination of historic range changes and reproductive mechanisms, as well as contemporary dispersal capabilities, may be responsible for the observed population genetic structures of A . diversus and C. humeralis . Accordingly, generalisations based on present‐day dispersal abilities alone may be misleading particularly for island habitats such as New Zealand where gene pools may already be restricted.

Relative importance of surface and subsurface movement on benthic community recovery in the Makaretu River, North Island, New Zealand - Reece T. Fowler (New Zealand Journal of Marine and Freshwater Research, 2002)
Colonisation of macroinvertebrates following changes to the stream environment occurs rapidly through drift, oviposition, lateral movement, and vertical migration. To assess the influence of different sources of colonists on benthic macroinvertebrate community composition, a colonisation experiment using artificial substrate baskets was conducted in the braided Makaretu River in the southern Hawke's Bay (North Island, New Zealand). Both the numbers of taxa and individuals rapidly increased through time in baskets only allowing drifting and surface crawling invertebrates (surface), baskets only allowing invertebrates migrating from the hyporheic zone (hyporheic), and baskets that allowed both (controls). The numbers of taxa and density of individuals indicated that the artificial substrate baskets were similar to the benthos after 14 and 28 days, respectively. However, overall benthic community composition was not similar to the surrounding benthos until Day 42 in all three basket treatments. The colonisation rates identified from artificial baskets in the Makaretu River are consistent with other colonisation experiments undertaken in New Zealand and overseas. Elmidae (Coleoptera) was most abundant within surface treatments until Day 28 after which Deleatidium spp. (Ephemeroptera) became dominant. The abundance of Elmidae and Deleatidium in the control treatments was consistent with colonisation patterns in the surface baskets. Deleatidium dominated baskets allowing access from the hyporheic zone throughout the experiment. It appears that Elmidae colonise quickly in greater numbers by drifting and/or crawling and Deleatidium colonises more slowly from the hyporheic zone, eventually replacing Elmidae as the most common animal. This indicates that the hyporheic zone provides a source of invertebrate colonists later during community recovery, whereas drifting and/or crawling provides colonists early during recovery.

Two‐phase stratified random surveys on multiple populations at multiple locations - Bryan F. J. Manly; Jo‐Anne M. Akroyd; Kim A. R. Walshe (New Zealand Journal of Marine and Freshwater Research, 2002)
The two‐phase random stratified sampling design proposed by Francis (1984) was designed for situations where prior information is insufficient to ensure an efficient allocation of sampling effort to different strata. It involves taking a first‐phase sample, and then using the data from this to allocate a second‐phase sample which compensates for any shortcomings of the first‐phase sample. Here we generalise this method to situations where several species are sampled simultaneously, and at several locations. The method then uses the first‐phase sample results to decide how best to allocate a second‐phase sample to locations and strata. We provide the results of a simulation study based on model populations of shellfish which demonstrates the effectiveness of the method. We use a survey of cockles, pipis, and tuatuas on 11 Auckland Fisheries Management Area beaches as an example of its use.

Effect of three conditioning diets on the fatty acid composition of gonads and muscle of Argopecten purpuratus - Hernán Palma‐Fleming; Jorge M. Navarro; Eduardo Peña; Gloria Martínez (New Zealand Journal of Marine and Freshwater Research, 2002)
Mature specimens of Argopecten purpuratus (Lamarck, 1819), obtained from the Culture Center of Tongoy Bay, northern Chile were conditioned at 20°C and fed three different diets (mixture of pure microalgae, microalgae supplemented with a lipid emulsion, and microalgae supplemented with carbohydrates). Fatty acids were analysed at 0, 18, 38, 58, and 72 days of gonad conditioning. Both muscle and gonads showed a significant decrease in the relative distribution (weight % of total fatty acids) of saturated, monounsaturated, and n‐6 polyunsaturated fatty acids (mg/g dry weight). Generally, an increase of the n‐3 polyunsaturated group was observed for gonads until Day 58, thereafter a decrease was observed, probably as a result of environmental stress. A similar trend was observed for eicosapentaenoic and docosahexaenoic acids. n‐3 polyunsaturated fatty acids were the most preserved fatty acids, suggesting their importance as essential fatty acids for gonad maturation. The lipid‐supplemented diet afforded the best gonadal maturation and spawning occurred after 72 days.

Natural diet of the seahorse Hippocampus abdominalis - Chris M. C. Woods (New Zealand Journal of Marine and Freshwater Research, 2002)
This investigation examined the diet of adult wild seahorses, Hippocampus abdominalis Leeson 1827, from Wellington Harbour, New Zealand. Diet of seahorses (n = 59) collected from shallow subtidal macroalgal stands consisted largely of crustaceans, in particular amphipods (e.g., caprellid and ischyrocerid amphipods), caridean shrimp (i.e., Hippolyte bifidirostris) , and peracarids (i.e., the mysid Tenagomysis similis) . There were no differences in diet between male and female seahorses. Smaller seahorses consumed a greater amount of crustaceans than larger seahorses, as a result of the greater proportion of amphipods in their gut contents. There were some seasonal differences in diet, with amphipod consumption peaking in spring and summer, and decapod consumption lowest in autumn.

Uptake of palytoxin‐like compounds by shellfish fed Ostreopsis siamensis (Dinophyceae) - Lesley Rhodes; Neale Towers; Lyn Briggs; Rex Munday; Janet Adamson (New Zealand Journal of Marine and Freshwater Research, 2002)
Greenshell™ mussels (Perna canaliculus Gmelin), scallops (Pecten novaezealandiae Reeve), and Pacific oysters (Crassostrea gigas Thunberg) were fed with a New Zealand strain of mass cultured Ostreopsis siamensis Schmidt (for 27 and 84 h and with 1.5 × 10 6 or 8.6 × 10 6 cells, respectively) under laboratory conditions. The microalgal cells contained 0.3 pg palytoxin equivalents cell –1 (as determined by the haemolysis neutralisation assay (HNA) of Bignami (1993)) and extracts of these cells were toxic to mice after intraperitoneal injection. No palytoxin‐like material was detected either in the hepatopancreas or the muscle and roe of mussels fed O. siamensis . Oysters contained detectable amounts of toxin in hepatopancreas muscle, and roe while higher concentrations were present in the hepatopancreas of scallops. Extracts of control shellfish (tested biotoxin free and not fed O. siamensis) were toxic to mice, and there was no definitive evidence that feeding shellfish with O. siamensis at the levels employed in the present experiment increased the toxicity of shellfish tissue extracts to mice.

Genetic differentiation between the New Zealand and Falkland Islands populations of southern blue whiting Micromesistius australis - A. W. Ryan; P. J. Smith; J. Mork (New Zealand Journal of Marine and Freshwater Research, 2002)
The southern blue whiting Micromesistius australis (Norman, 1937) is found in two geographically distinct areas, the South Atlantic and south‐west Pacific Oceans. To date there has been no appraisal of the genetic relationships between the populations in these two areas. Here, we present analyses of New Zealand and Falkland southern blue whiting using mini‐ and microsatellite loci. Two out of six loci show highly significant allele frequency heterogeneities between the two areas, strongly suggesting genetically distinct populations.

Antarctic Intermediate Water variability in the northern New Zealand region - Basil R. Stanton (New Zealand Journal of Marine and Freshwater Research, 2002)
In the region between 30°S and northern New Zealand, vertical salinity profiles through the core of the Antarctic Intermediate Water (AAIW) show a high degree of spatial and temporal variability, and this variability is much larger than that found in nearby ocean areas. Characteristic features are interleaving of salinity layers and large changes in the salinity minimum between adjacent stations. Quantifying the changes through the calculation of an intrusion index highlights the degree of variability and the importance of boundary mixing along the New Zealand slope. However, the main cause of the variability is the meeting and mixing of higher salinity AAIW, arriving from the north‐west (having travelled around the subtropical gyre) with lower salinity AAIW arriving by more direct entry from the north‐east. These waters meet in the region through the action of the meso‐scale eddy field. Present data indicate that where strong salinity interleaving occurs, the length scales are of the order of 10 km and the time scales are of the order of a few days. Resolution of the processes at work will require studies on finer scales than presently available.

Use of the SHMAK clarity tube for measuring water clarity: Comparison with the black disk method - Cathy Kilroy; Barry J. F. Biggs (New Zealand Journal of Marine and Freshwater Research, 2002)
A metre‐long transparent tube for measuring visual water clarity was developed as part of the New Zealand Stream Health Monitoring and Assessment Kit (SHMAK) for use by non‐scientists. Water clarity measured using the tube (the horizontal sighting range of a black target) was compared with that measured using the standard “black disk” method (in which a black target is viewed horizontally underwater) to determine the feasibility of estimating black disk clarities from clarity tube readings. Readings using the two methods showed good agreement for waters with clarity c. 50 cm are lower than the black disk visibility and follow a logarithmic relationship with visibility, which enables useful readings to be made in clearer water. Independent testing of the relationship showed that black disk visibilities may be predicted with reasonable confidence in waters that contain very low concentrations of dissolved humic materials (yellow substance). In waters that are noticeably brown‐coloured, the relationship is less consistent especially at black disk visibilities of more than 1.5 m. Recommendations are given for the use of the clarity tube.

Two new species of Pseudostomella (Gastrotricha: Macrodasyida) with scaled triancres from the east coast of Australia - Rick Hochberg (New Zealand Journal of Marine and Freshwater Research, 2002)
Two new species of Pseudostomella from North Stradbroke Island, Australia, P. klauserae n. sp. and P. megapalpator n. sp., are characterised by scaled triancres, cuticular structures that until now were known only from one other member of the genus. The structure of the scaled triancres in both species is new: the triancre base is diamond‐ or triangular‐shaped with three shafts that arise to form feather‐like scales. P. klauserae n. sp. is characterised by scales arising from a diamond‐shaped triancre base, the distribution of cephalic papillae, and the abundance and distribution of anterior and lateral adhesive tubes. P. megapalpator n. sp. is distinguished by scales arising from a rounded‐triangular triancre base, large dorsal, digitiform papillae, and ventral adhesive tubes. The presence of two new species with scaled triancres allows for the formation of a novel species complex within the genus. An amended key to the species is included.

Pfiesteria shumwayae (Pfiesteriaceae) in New Zealand - Lesley L. Rhodes; Joann M. Burkholder; Howard B. Glasgow; Parke A. Rublee; Coy Allen; Janet E. Adamson (New Zealand Journal of Marine and Freshwater Research, 2002)
Pfiesteria shumwayae Steidinger et Burkholder is now known to be present in New Zealand and occurs in estuaries around the country. The presence of Pfiesteria was initially determined by a polymerase chain reaction (PCR)‐based detection assay, using oligonucleotide primers targeted at ribosomal DNA extracted from estuarine water and sediments. Presence was confirmed by isolation from fresh sediments in the presence offish (Oreochromis mossambicus) , followed by identification by scanning electron microscopy. The New Zealand isolates of P. shumwayae were ichthyotoxic in bioassays, but there is no historic evidence offish kills in New Zealand associated with the dinoflagellate.

Effects of sediment on fish communities in East Cape streams, North Island, New Zealand - J. Richardson; I. G. Jowett (New Zealand Journal of Marine and Freshwater Research, 2002)
We examined the effects of sediment on fish communities at 38 sites in the East Cape region of New Zealand. Many streams in this region are subject to high sediment loads, a natural situation that has been exacerbated by the conversion of native forest to pasture. The fish community consisted of diadromous native species common throughout New Zealand that require access to and from the sea. We found that site altitude and distance inland were important factors in determining the abundance and composition of the fish community. We used four measures as indices of sediment load: suspended sediment concentration, median substrate size, substrate stability, and the ratio of the wetted width to the width of the active (non‐vegetated) stream channel. Although all indices were correlated, the ratio of wetted width to width of active channel was most closely related to fish abundance and diversity. Fish abundance and diversity reduced as sediment load increased among streams, with up to nine fish species in streams with low sediment loads and only two species in streams with high sediment loads. In‐stream habitat also varied with sediment load; as load increased, depth and substrate size decreased and velocity increased. These results suggest that activities that increase sediment loads in rivers will have a negative impact on native fish communities in New Zealand.

Abundance of brown trout as related to littoral zone gradient in Lakes Te Anau and Manapouri, New Zealand - Rick J. Stoffels; Gerard P. Closs (New Zealand Journal of Marine and Freshwater Research, 2002)
Adult brown trout ( Salmo trutta L.) in lakes are primarily littoral/benthic foragers. We predicted that the distribution of adult brown trout in lakes would be shaped by foraging demands, and that they would be more abundant in gently sloping littoral areas, that is, littoral areas that have a greater space available to support benthic foraging habitats. To address this hypothesis, we measured abundance of brown trout among littoral areas with different gradients in Lakes Te Anau and Manapouri. There was a significant negative relationship between littoral zone gradient and relative abundance (CPUE) of adult brown trout. This result supports the hypothesis that brown trout aggregate in littoral areas with greater amounts of foraging habitat in Fiordland lakes.

Nitrate movement and removal along a shallow groundwater flow path in a riparian wetland within a sheep‐grazed pastoral catchment: Results of a tracer study - Douglas A. Burns; Long Nguyen (New Zealand Journal of Marine and Freshwater Research, 2002)
The movement and removal of nitrate (NO 3 ‐ ) along a groundwater flow path within a riparian wetland was investigated during a 24‐day period in late autumn‐early winter, using a lithium bromide (LiBr)‐potassium nitrate (KNO 3 ) tracer solution containing 19 200 mg/litre as Br ‐ and 193.8 mg/litre as NO 3 ‐N. The tracer solution was added as an instantaneous dose of tracer solution at a depth of 10–20 cm to four injection wells in two 1 m 2 plots within a sheep‐grazed pastoral catchment at the Whatawhata Agricultural Research Centre near Hamilton, New Zealand. Bromide and NO 3 ‐N concentrations were measured periodically in: (1) wetland groundwater samples from piezometers installed at 15 and 30 cm depths and located at 30, 60, and 100 cm down gradient from the injection wells; and (2) surface flow samples. Peak concentrations of 50–250 mg/litre of Br ‐ and 0.2–1.1 mg/litre of NO 3 ‐N were reached within 1–2 days after application at most piezometers. Nitrate concentrations decreased thereafter more sharply than did those of Br ‐ , resulting in decreased NO 3 ‐N/Br ‐ ratios from Days 2 through 7. More than 99% of groundwater samples collected after the tracer application had NO 3 ‐N/Br ‐ less than the value in the tracer solution indicating removal of NO3‐N during transport. Mass flux estimates indicated removal of >90% of added NO 3 ‐N along the 100 cm flow path from the injection, with essentially all of the NO 3 ‐ removed within the first 30 cm of transport. On Days 10 and 24, just after rain events, surface flow from the experimental plots had greatly elevated NO 3 ‐N concentrations that were not accompanied by correspondingly elevated Br ‐ concentrations, indicating that NO 3 ‐N originating from the surrounding catchment was transported over the wetland surface with little penetration or mixing with wetland groundwater. Despite a significant capacity for NO 3 ‐N removal from shallow groundwater equivalent to an annualised value of 50 kg/ha in these wetland study plots, large amounts of NO3‐N from the catchment are likely to move over the wetland surface during rain events without adequate soil contact time for efficient denitrification and retention.

Spatial and temporal distribution of landlocked Galaxias maculatus and Galaxias platei (Pisces: Galaxiidae) in a lake in the South American Andes - Juan P. Barriga; Miguel A. Battini; Patricio J. Macchi; Daniela Milano; Victor E. Cussac (New Zealand Journal of Marine and Freshwater Research, 2002)
Galaxiids are present in many of the Andean lakes in southern South America. We studied landlocked Galaxias maculatus (Jenyns) and Galaxias platei Steindachner populations in a deep oligotrophic lake (Lake Gutiérrez, Patagonia, Argentina). Their temporal and spatial distribution, intralacustrine movements (horizontal and vertical), and spawning periods were analysed using several sampling techniques (ichthyoplankton net, seine net, gill net, and baited benthic taps). We identified the early life stages of both species based on their morphology and otolith shape. The free embryos of both species migrate to the limnetic zone, where they coexist as larvae, facing the same food availability and probably the same predation risk. Each species then moves on to its own juvenile and adult habitat: the littoral and benthic zone for G. maculatus and only the deeper benthic zone for G. platei . Their adult habitats and part of their spawning periods partly overlap.

Two new species of Turbanellidae (Gastrotricha: Macrodasyida) from a high‐energy beach on North Stradbroke Island, Australia - Rick Hochberg (New Zealand Journal of Marine and Freshwater Research, 2002)
s Two new species of macrodasyidan gastrotrichs were found in coarse intertidal sands of Frenchmans Beach, a high‐energy beach facing the South Pacific Ocean, on the eastern side of North Stradbroke Island, Australia. Paraturbanella stradbroki n. sp. is up to 665 μm long and is distinguished from its congeners by the shape of the head, the presence of dorsal and lateral adhesive tubes, the pattern of locomotor cilia, and the lack of piston pits and a median caudal cone. Turbanella brusci n. sp. is up to 1002 μm long and is characterised by the shape of the head, the presence of three paired columns of dorsal, lateral, and ventrolateral adhesive tubes, a median caudal cone, and the lack of “cirrata” tubes. The ventrolateral adhesive tubes are symmetrically aligned beneath the lateral adhesive tubes and are considered unique to the genus. This constitutes the first report of Paraturbanella and Turbanella from Australian waters.

Water quality and sediment and nutrient export from New Zealand hill‐land catchments of contrasting land use - John M. Quinn; Morag J. Stroud (New Zealand Journal of Marine and Freshwater Research, 2002)
Measurements were made of suspended sediment (SS), volatile suspended solids, dissolved organic carbon (DOC), nitrogen (N) and phosphorus (P) concentrations, turbidity, black disk visibility, pH, alkalinity, and temperature, at monthly intervals for 2–5 years on nine streams draining catchments with pasture, pine plantation, and native forest land uses. Stream flow and flow‐weighted concentrations of SS, N, and P were also measured for up to 2 years from pasture, native forest, and mixed land‐use catchments enabling calculation of export (kg ha ‐1 yr ‐1 ). During 1996–97, export from the pasture stream was 2.5‐ to 7‐fold higher for SS (988), total P (1.50), total Kjeldahl N (5.65), nitrate N (4.37), and ammoniacal N (0.34) than from the stream draining native forest. In contrast, export of DOC (25.5) and dissolved reactive P (DRP) (0.25) from the pasture stream were within 20% of the native stream's values. Export of SS and nutrients (except DRP) from the pasture catchment was 4‐ to 15‐fold higher during the winters of 1995 and 1996 than winter 1997 when rainfall was half the normal level. Streams draining native forest had lower temperature, sediment, and nutrient concentrations (except DRP), and higher water clarity, than those draining pine forest and pasture. A pine/scrub stream had the highest SS and turbidity and lowest DRP, pH, and alkalinity. Pasture streams had the highest concentrations of all N species (geometric means 2‐to 4‐fold > native), total P, and DOC, and also showed the greatest variation in water quality attributes in relation to season and flow. The influences of land use were attributable to differences in both source materials of sediment and nutrients available for transport and changes in rates of in‐stream processing.

Temperature and salinity mean and variability within the subtropical front over the Chatham rise, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2002)
Estimates are made of the mean and variability in temperature and salinity across the Subtropical Front along 178°30'E, east of New Zealand. These estimates are made from six sections taken over 5 years, but biased towards spring and autumn sampling. Monte‐Carlo simulations of the potential errors introduced by this sampling suggest that the mean fields can be reasonably well determined, but the annual cycles have large relative error. April 1999 residuals were anomalously warm and saline compared with the other five sections. These anomalies may be linked to an increased strength of the Wairarapa Eddy at that time.

Occurrence of dolphinfish ( Coryphaena hippurus ) and pompano dolphinfish ( Coryphaena equiselis ) in the Canary islands revealed by genetic analysis - J. M. Pujolar; C. Pla (New Zealand Journal of Marine and Freshwater Research, 2002)
Genetic analyses of samples of the genus Coryphaena caught in the Canary Islands clearly revealed the existence of two different species, C. hippurus , Linnaeus 1758 and C. equiselis , Linnaeus 1758. Each species was fixed for different alleles at 11 out of 30 loci and a large genetic distance (0.814) was found between the two species. Previously only C. hippurus has been reported in the Canary Islands fishery. The two Coryphaena species are similar in appearance, so C. equiselis can be confused with C. hippurus by fishers, especially small specimens C. hippurus and C. equiselis .

Diet of giant kokopu, Galaxias argenteus - Martin L. Bonnett; Paul W. Lambert (New Zealand Journal of Marine and Freshwater Research, 2002)
The stomach contents of 105 preserved specimens of giant kokopu, Galaxias argenteus (Gmelin 1789), collected from various locations around New Zealand between c. 1963 and 1994, were used to investigate giant kokopu diet. A total of 76 food taxa, predominantly invertebrates, were identified and categorised as either of aquatic or terrestrial origin from the 91 stomachs that contained food items. Aquatic Trichoptera, Gastropoda, and Hemiptera comprised 29.1, 12.6, and 14.4% by abundance respectively, and terrestrial Coleoptera 12.2% by abundance. Adult terrestrial Coleoptera were the most commonly occurring taxa, and were found in 59% of the stomachs that contained food. Food items of aquatic origin occurred in 94.5% of the giant kokopu stomachs that contained food and comprised 74.9% of the items by abundance. Although fewer items of terrestrial origin were encountered, they nevertheless appeared to be a significant component of the diet, and occurred in 83.5% of the giant kokopu stomachs that contained food, and comprised 25.1% of the items by abundance. Items of terrestrial origin occurred slightly more frequently in giant kokopu from lotic habitats than from lentic habitats. The significance of terrestrial food may be associated with giant kokopu preference for habitats with riparian cover. Fish also appeared to be a significant component of the diet, as 26% of the giant kokopu examined contained fish remains. Giant kokopu are probably best described as generalist feeders, as they utilise a wide range of foods of both aquatic and terrestrial origin.

Ocean‐tide loading and Earth tides around New Zealand - Derek G. Goring; Roy A. Walters (New Zealand Journal of Marine and Freshwater Research, 2002)
Cotidal charts of ocean‐tide loading and Earth tides for the New Zealand region are presented for eight constituents (M 2 , S 2 , N 2 , K 2 , K 1 , O 1 , P 1 , Q 1 ). Ocean‐tide loadings were calculated by evaluating a convolution integral between tide models (global and local) and a Green's function that describes the response of the Earth to tide loading. Earth tides were calculated from the tide‐generating potential. The ocean‐tide loadings are a maximum to the north of New Zealand for M 2 and N 2 and in the western Cook Strait region for S 2 and K 2 . The diurnal ocean‐tide loadings are dominated by amphidromes east of the Chatham Islands (K 1 and P 1 ) and north of Bay of Plenty (O 1 and Q 1 ). Diurnal Earth tides are a maximum at 45°S and vary only slightly in amplitude and phase over New Zealand; semidiurnal Earth tides increase from south to north.

In‐stream habitat suitability criteria for feeding inanga ( Galaxias maculatus ) - I. G. Jowett (New Zealand Journal of Marine and Freshwater Research, 2002)
Inanga ( Galaxias maculatus Jenyns) are the basis of an important recreational and commercial freshwater fishery that has declined over the past 100 years, probably because of habitat degradation in developed areas. Maintenance of suitable stream flows for inanga is one means of protecting the fishery. Observations of habitat use by drift‐feeding inanga were made in three streams. Most feeding inanga were stationary in the current taking food items from the drift and sometimes from the surface. Drift‐feeding locations were related to current patterns and water velocity, with inanga feeding at locations where the current concentrated food, and where water velocities were sufficiently low to allow the fish to hold position. The mean feeding velocity did not vary significantly between streams, although the range of velocities used did. Optimum feeding velocities were 0.03–0.07 m s ‐1 , and were comparable with brown trout ( Salmo trutta ) feeding velocities, when adjusted for the differences in fish size. Depth use was very different between streams and this was attributed to the variation in available habitat. Depths greater than 0.3 m were optimum, with some use of depths between 0.1 and 0.3 m. It is suggested that inanga suitability criteria are dictated by biological factors, such as swimming ability and bio‐energetic requirements, rather than the river the fish is living in and that it is necessary to collect habitat use and availability data in a wide range of stream types to define optimal habitat and suitability criteria for generalised application.

Effect of storm drain discharge on the soft shore ecology of Porirua Inlet, New Zealand - Kathryn J. Botherway; Jonathan P. A. Gardner (New Zealand Journal of Marine and Freshwater Research, 2002)
The effect of storm drain discharge on the ecology of the soft shore community near the Semple Street outfall in Porirua Inlet, New Zealand, was investigated from December 1998 to April 1999. Biological community structure, sedimentary properties, and heavy metal concentrations of surficial sediments were examined at increasing distance (5, 90, 140 m) from the storm drain at two (upper and lower) shore heights (total of six sites). Concentrations of copper (Cu), lead (Pb), and zinc (Zn) at nine sites from the storm drain to the mouth of the inlet were estimated in April 1999. Typically, mean numbers of individuals decreased, whereas mean numbers of taxa, and the Shannon‐Wiener diversity index increased with increasing distance from the storm drain. Analysis of variance revealed that the 5, 90, and 140 m sites at both tidal heights exhibited small but significant differences in community structure which were attributable to differences in species abundance, rather than to differences in the suite of species which characterise these sites. It was not possible to identify temporal trends in the data set. Analysis of similarities revealed significant differences in species abundance among the three sites for the high shore, the low shore, and both tidal heights combined. Sites furthest apart (5 versus 140 m) exhibited the greatest, and sites closest together (90 versus 140 m) exhibited the least, difference in biological community structure, suggesting that storm drain outflow modifies benthic community composition immediately in front of the drain and up to

Detecting patterns in hyporheic community structure: Does sampling method alter the story? - M. R. Scarsbrook; J. Halliday (New Zealand Journal of Marine and Freshwater Research, 2002)
Hyporheic invertebrates were sampled in six small headwater streams draining pine, pasture, and native forest catchments. Sites were sampled in autumn and spring using three different hyporheic sampling methods (colonisation pots, pump sampling, and freeze‐coring). Total invertebrate abundance and taxon richness differed significantly among sites on both sampling occasions for pump samples, whereas freeze‐coring did not discriminate among sites, and pot samples showed significant differences in autumn, but not in spring. Differences among sites with respect to community composition were not consistent between sampling methods. Community ordination indicated that samples from colonisation pots tended to group together, whereas pump and freeze core samples were widely separated. Differences across land uses were also apparent (native forest sites formed a distinct cluster separated from pine and pasture sites). Results suggest that colonisation pots may provide a pathway for the entry of epigean organisms into the hyporheic zone even when hydraulic connectivity between surface and hyporheic zones is low. Invertebrate abundance was very low in pump samples, and this method also captured the fewest taxa of the three methods. The size bias known to exist with pump sampling techniques may restrict the usefulness of the method when comparing streams of differing hydraulic conductivity.

Wairarapa Coastal Current influence on sea surface temperature in Hawke Bay, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2002)
The Wairarapa Coastal Current (WCC) flows along the east coast of the North Island, New Zealand. This current has been relatively little studied, and there are few direct measurements of its mean and variability. Here, an indirect method is used to gain some insight into the WCC variability and its effect on coastal temperature. Eight years of coastal temperature from Napier in Hawke Bay are modelled as a bivariate linear expansion of alongshore windstress and solar radiation. In the frequency domain, the modelled temperatures are coherent with observed temperatures, and in the time domain, they are positively correlated for 80% of the time. The model results suggest both that variations in the WCC are wind‐driven, and that alongshore advection accounts for most of the temperature change at Napier. Periods when the modelled temperature is not correlated with observed temperature could be because of episodes of enhanced upwelling, or large‐scale influences breaking down the alongshore temperature gradient.

Distribution and biomass of benthic microalgae in Manukau Harbour, New Zealand - L. B. Cahoon; K. A. Safi (New Zealand Journal of Marine and Freshwater Research, 2002)
Benthic microalgal biomass (as sediment chlorophyll a (Chl. a ), by spectrophotometry) and taxonomic composition (by HPLC pigments analysis) were investigated at intertidal locations throughout Manukau Harbour, North Island, New Zealand. Benthic microalgal biomass averaged 97.5 mg Chl. a m ‐2 for all sediment samples. Benthic microalgal biomass was higher in sediments containing at least some sand than in muddy sediments, in contrast to previous findings from Manukau Harbour. Loading of fine sediments from erosion within the harbour's basin may, therefore, affect the amount and distribution of benthic microalgal biomass in the harbour. Average benthic microalgal biomass for the entire area of the harbour was at least 62.5 mg Chl. a m ‐2 . The latter value is at least 4 times higher than mean annual, spatially integrated phytoplankton biomass in Manukau Harbour, suggesting that benthic microalgae are a more important food source for estuarine consumers. High fucoxanthin:chlorophyll a ratios indicated that benthic microalgae were primarily diatoms. The physical characteristics of Manukau Harbour and similarity in taxonomic composition of the phytoplankton and benthic microalgae suggest that resuspended benthic microalgae are an important component of the harbour's phytoplankton biomass.

Use of classification and regression tree (CART) analysis with chemical faecal indicators to determine sources of contamination - Jan Gregor; Nick Garrett; Brent Gilpin; Cliff Randall; Darren Saunders (New Zealand Journal of Marine and Freshwater Research, 2002)
Both human and non‐human faecal contamination of environmental waters pose a risk to human health that can be reduced if the source can be identified and responsibility for mitigation accepted. Traditional microbiological indicators are rarely adequate for source identification but some chemical indicators offer promise. In this work, the similarities and differences of selected chemical profiles of different faecal effluent types have been modelled using classification and regression tree (CART) analysis. Human effluents can be distinguished from non‐human effluents by the presence of fluorescent whitening agents, and the concentrations or ratios of concentrations of the faecal stanols coprostanol and 24‐ethylcoprostanol can distinguish most of the non‐human effluent types considered. To allow for the effect of variable dilution when effluents enter environmental waters, ratios of concentrations will be required to establish a model, and a model more complex than CART will be required to apportion multiple effluent‐type contamination.

Influence of diet and temperature on physiological energetics of Chorus giganteus (Gastropoda: Muricidae) during reproductive conditioning - J. M. Navarro; G. E. Leiva; C. S. Gallardo; C. Varela (New Zealand Journal of Marine and Freshwater Research, 2002)
The influence of two bivalve diets ( Mytilus chilensis “chorito” and Tagelus dombeii “navajuela”) at three temperatures (13, 15, and 18°C) was studied during the reproductive conditioning of Chorus giganteus (Lesson, 1829). Energy budgets were determined taking into account energy acquisition (ingestion and absorption) and energy expenditure (oxygen consumption, ammonia production, and energy placed into mucus production and egg laying). Relative physiological condition was assessed by calculating the scope for growth index (SFG). Diet and temperature both played key roles in the physiological energetic and reproductive conditioning of this snail. Tagelus was the preferred prey, probably because of its greater vulnerability to predatory attack by C. giganteus . The highest feeding rate was observed at 15°C, coinciding with optimal growth. Absorption efficiency was similar with both diets, despite the differential preference in prey. Temperature had no effect on oxygen uptake, but increased as the snails fed on Tagelus during the reproductive conditioning period. Diet was the main factor affecting SFG, and temperature, although significant, accounted for a lower percentage of variation in SFG. Highest growth rates were observed at 15°C on a Tagelus diet. Reproductive effort, measured as the proportion of the total energy budget of an organism that is allocated to reproduction, was highest at 18°C with a Tagelus diet. Energy would not be allocated for reproduction when the snails were fed with M. chilensis , as SFG was negative at all three temperatures.

A new species of bathyal elasipod sea cucumber from New Zealand (Echinodermata: Holothuroidea) - David L. Pawson (New Zealand Journal of Marine and Freshwater Research, 2002)
Orphnurgus dorisae new species is described from bathyal depths to the north of New Zealand, near the Kermadec Islands. It is distinctive in possessing spatulate rods and spinous rods dorsally, and spinous rods and perforated plates ventrally. A key to Orphnurgus species is provided. Egg size suggests that this species, and other Orphnurgus species, may have planktonic lecithotrophic embryos.

Sink rate of baited hooks during deployment of a pelagic longline from a New Zealand fishing vessel - Simon Anderson; Brian Mcardle (New Zealand Journal of Marine and Freshwater Research, 2002)
The sink rate of baited hooks during the deployment of a pelagic longline was determined using time depth recorders. This study was undertaken to determine how long baited hooks are within the known diving ranges of seabirds. During the vessel's normal fishing operations the unweighted baited hooks reached a mean depth of 5.57 m, 30 s after being deployed. The tori line aerial section covered the longline for a mean time of 29.3 s. With the addition of a 60 g lead swivel, the mean baited hook depth attained more than doubled to 13.44 m, and a further trial using a lead core cord in the snood configuration showed a small but significant increase in hook depth over the unweighted control (7.27 m). An increase in wind speed caused the baited hooks to sink faster (0.54 m for each Beaufort unit increase in wind speed). There was also evidence that the apparent wind direction while the vessel is setting also has an effect on the depths realised, but swell height had no detectable effect. The temperature of the bait also significantly affected the hook depth: partially thawed baits sank faster than thawed baits. A 1°C rise in bait temperature reduced the depth by 0.19 m. During normal line setting on this vessel using unweighted branchlines and a tori line, a considerable proportion of the baited hooks are within the known diving range of sooty shearwaters (Puffinus griseus) , white chinned petrels (Procellaria aequinoctialis) , shy albatross (Thalassarche cauta) , black browed albatross (T. melanophrys) , grey headed albatross (T. chrysostoma) , and light mantled sooty albatross (Phoebetria palpebrata) . The addition of a 60 g weight removes the baited hooks from the recorded diving range of all of these species except sooty shearwaters. Investigating the behaviour of different gear configurations along with evaluating the effect that environmental conditions have on the deployment of a longline will greatly add to our understanding of why some seabirds are caught.

Effects of logging with and without riparian strips on fish species abundance, mean size, and the structure of native fish assemblages in Coromandel, New Zealand, streams - David K. Rowe; Joshua Smith; John Quinn; Ian Boothroyd (New Zealand Journal of Marine and Freshwater Research, 2002)
We determined the effects of logging, both with and without a riparian buffer strip, on the native fish fauna at 27 stream sites in an exotic pine (mainly Pinus radiata) forest on the Coromandel Peninsula, New Zealand. Fish abundance at the logged sites was compared with reference sites in both unlogged pine and native forest. The abundance of Anguilla dieffenbachii (Gray) and Anguilla australis (Richardson) was not significantly affected by logging. However, the abundance of Galaxias fasciatus (Gray) and Gobiomorphus huttoni (Ogilby) was. There were fewer Ga. fasciatus at the logged sites without buffers than at the reference sites, but more at the logged sites with buffers. The abundance of Go. huttoni was higher at the logged sites than at the reference sites, and was highest at the logged sites with riparian buffers. Overall, the different, species‐specific responses to logging maximised total fish numbers at the logged sites. As total fish numbers, the abundance of Ga. fasciatus , and species equitability, a measure of fish assemblage structure, were all highest at the logged sites with riparian buffer strips, we concluded that riparian strips enhanced the native fish community of streams within these logged catchments.

Response of New Zealand waters to the Peru tsunami of 23 June 2001 - Derek G. Goring (New Zealand Journal of Marine and Freshwater Research, 2002)
The Peru tsunami of 23 June 2001 arrived at New Zealand's east coast 16.5 h after generation, having travelled c. 8000 km across the Pacific Ocean. All the sea level recorders on the east coast recorded waves, but the response was highly variable, with the greatest response in Lyttelton Harbour, where the water fell by 26 cm, then rose over the next hour to peak at 30 cm. None of the recorders on the west coast felt the tsunami. The time scale of the waves was between 2 and 20 min and they persisted for more than 20 h after the first waves arrived, before starting to slowly decay. In some places, like Pegasus Bay, the tsunami excited local seiche, but these waves quickly dissipated. Analysis of data collected at 1‐min intervals, instead of the standard 5‐min intervals, indicated that information is lost when sampling tsunami at 5‐min intervals.

Movements and habitats of adult lamprey ( Geotria australis) in two New Zealand waterways - D. J. Jellyman; G. J. Glova; J. R. E. Sykes (New Zealand Journal of Marine and Freshwater Research, 2002)
The spring upstream spawning migration of the Southern Hemisphere lamprey, Geotria australis Gray, was investigated by monitoring movements of radio‐tagged lampreys in two South Island, New Zealand, catchments of contrasting size (Okuti Stream, a small coastal stream and the Mataura River, a medium‐sized lowland river). A total of 65 lampreys were radio‐tagged and tracked by foot and helicopter between 1998 and 1999. Retention of the externally‐mounted tags proved a problem, and lampreys were tracked for a maximum of 56 days. Most movement was recorded within a few days of release; movement was generally up stream although a number of fish also periodically moved down stream. Maximum daily movement in the Okuti Stream was 0.45 km compared with 12.6 km in the Mataura River; upstream movement was stimulated by increased flow but curtailed by large floods. During the day, lampreys were generally associated with bankside debris cover. The seven fish that moved furthest up the Mataura River all entered the same tributary, presumably in response to odours of their conspecifics. Thirteen lampreys retained for a year and released as nearly sexually mature, moved little from their place of liberation and possible reasons for this are discussed.

Taxonomic revision of the genus Latrunculia Du Bocage (Porifera: Demospongiae: Latrunculiidae) in New Zealand - Belinda Alvarez; Patricia R. Bergquist; Christopher N. Battershill (New Zealand Journal of Marine and Freshwater Research, 2002)
The genus Latrunculia in New Zealand was believed to be represented by at least three species: L. brevis Ridley & Dendy and two undescribed species. However, results from recent studies indicate that the genus contained a complex of at least eight genetically distinct species. In this paper we revise the taxonomy of Latrunculia in New Zealand and describe nine new species. Eight of these were previously identified using genetic techniques (i.e., L. kaakaariki sp. nov., L. duckworthi sp. nov., L. procumbens sp. nov., L. wellingtonensis sp. nov., L. kaikoura sp. nov., L. triverticillata sp. nov., L. fiordensis sp. nov., and L. millerae sp. nov.) and one (L. oxydiscorhabda sp. nov.) was distinguished based only on morphological differences. The species described fall into two morphological groups, spinispiraefera and triverticillata , which can be diagnosed by the number of whorls present along the discorhabd axis. The status of L. brevis , and other subantarctic species (i.e., Latrunculia bocagei, L. antarctica, L. lendenfeldi, L. spinispiraefera) is discussed; all of these species are considered to be valid but not conspecific with any of the species described here.

Evaluation of invertebrate biometrics and the influence of subsample size using data from some Westland, New Zealand, lowland streams - Ian C. Duggan; Kevin J. Collier; Paul W. Lambert (New Zealand Journal of Marine and Freshwater Research, 2002)
The accuracy and variability of six invertebrate biometrics (taxa richness, number of Ephemeroptera, Plecoptera, and Trichoptera (EPT) taxa, % EPT abundance, % dominant taxon, the Macroinvertebrate Community Index (MCI), and Quantitative MCI (QMCI)) were examined using data from four Westland, New Zealand, streams. All metrics except QMCI differed significantly among sites. Taxa richness and number of EPT taxa distinguished the most impacted site from the remaining sites. Significant temporal differences among streams occurred for % EPT abundance and MCI, and there were interaction effects for these plus % dominant taxon and QMCI, indicating that any differences among sites varied through time. Within individual streams, MCI and QMCI had low ( Metric values obtained from random 100‐count subsamples with replacement had low variability (

Effects of turbidity on the feeding ability of adult, riverine smelt ( Retropinna retropinna) and inanga ( Galaxias maculatus) - David K. Rowe; Joshua Smith; Erica Williams (New Zealand Journal of Marine and Freshwater Research, 2002)
Laboratory tank experiments indicated that turbidity levels up to 160 Nephelometric Turbidity Units (NTU) did not reduce the feeding rates of adult smelt ( Retropinna retropinna Richardson), or inanga (Galaxias maculatus Jenyns), on Daphnia sp. Mean feeding rates were higher for inanga than for smelt. However, the lower rates for smelt were related to the greater variation in individual feeding rates. Specifically, a few fish fed intensively while most did not. As the feeding ability of both species was unaffected by turbidity levels up to 160 NTU, they were less sensitive to turbidity than juvenile banded kokopu ( Galaxias fasciatus Gray). Juvenile banded kokopu should therefore be used as the benchmark species for setting turbidity guidelines to protect native fish in rivers where this species is present. Both juvenile and adult rainbow trout ( Oncorhynchus mykiss Richardson) appear to be more sensitive to turbidity than adult inanga and smelt, so should be used as benchmark species in all other waters.

Selected trace elements in Stockton, New Zealand, waters - E. Alarcón León; R. G. Anstiss (New Zealand Journal of Marine and Freshwater Research, 2002)
Ni, Mn, As, Pb, Cd, Cr, Cu, Hg, Se, Al, Zn, Fe, SO 4 2‐ , hardness (calc.) in addition to pH, total dissolved solids (TDS), and total suspended solids (TSS) were measured at 18 (11 surface and 7 subsurface) sampling sites (which were each assigned a semi‐quantitative Mudstone Index (MI)) from 20 days over 9 months in the waters which drain the Stockton coal mine area on the Stockton Plateau, New Zealand. Trace element, TDS and TSS concentrations were found to be elevated and pH depressed consistent with acid mine drainage (AMD) and were characterised by significant variability due to environmental processes. Frequent concentration spikes in surface and subsurface waters occurred which sometimes exceeded maximum acceptable values (MAV) and/or aesthetic guideline values (GV) including a number of toxic trace elements. Mean concentrations of Ni and Mn in both surface and subsurface waters and As and Cd in subsurface waters exceeded MAVs. Mean concentrations of Mn, Al, Fe, SO 4 2‐ , and pH in both surface and subsurface waters exceeded GVs. There tends to be higher trace element and TDS concentrations where there are more mudstones (higher MI) with lower pHs. It is recommended that any further studies focus on geographic distribution, concentration fluctuation factors, movement, and possible exposure issues.

Diet of the crayfish Paranephrops zealandicus in bush and pasture streams: Insights from stable isotopes and stomach analysis - John W. Hollows; Colin R. Townsend; Kevin J. Collier (New Zealand Journal of Marine and Freshwater Research, 2002)
Crayfish ( Paranephrops zealandicus White) stomachs from streams in both native bush (mainly tree leaves and dicotyledonous seeds) and exotic pasture settings (mainly grass stems and monocotyledonous seeds) were dominated by allochthonous material. More detritus occurred in stomachs in autumn‐winter than in spring‐summer, but quantities were similar in crayfish from native bush and pasture streams. The stomachs of larger crayfish contained a significantly greater proportion of detritus than smaller individuals. Aquatic invertebrates were the second most abundant dietary category by volume, with highest values in winter, but there were no significant differences between land uses or crayfish size classes. A wide range of invertebrates was eaten by crayfish, with mayfly nymphs, chironomid larvae, and snails predominating. The latter were numerically more prominent in crayfish from bush than pasture streams. Terrestrial invertebrates were recorded from 4% of stomachs, but there were no significant differences in relation to land use, season, or crayfish size class. Despite aquatic invertebrates making up 13 C and perhaps of microfloral origin, seems to be an important energy source for crayfish in both stream types.

Influence of fluctuating lake levels and water clarity on trout populations in littoral zones of New Zealand alpine lakes - Gavin D. James; Eric Graynoth (New Zealand Journal of Marine and Freshwater Research, 2002)
Brown trout (Salmo trutta Linnaeus 1758) and rainbow trout (Oncorhynchus mykiss Richardson 1836) populations in littoral zones of eight South Island, New Zealand alpine lakes were compared using gill and seine net sampling during summer. Lakes were selected to provide a matrix of lake level and water clarity variations and to assess how these variables influenced trout abundance (as reflected by catch rate), depth distribution, and size. Brown trout were small and in poor condition in three turbid lakes with shallow littoral zones and were scarce in one of these with a 14 m fluctuation. Although brown trout condition was generally higher in clear lakes, Lake Wanaka fish were an exception. Trout depth distribution was positively related to depth of the littoral zone. Brown trout were caught at most depths whereas rainbow trout showed variable depth preferences in different lakes. Rainbow trout catch rate, weight, and condition factor were unrelated to differences in depth of the littoral zone or lake level fluctuations, and it was concluded that spawning success and limnetic food supplies may be more important for this species. Spawning interactions may account for the different species composition between the stable clear Lake Wanaka, and the adjacent fluctuating clear Lake Hawea. Moderate and slow lake level fluctuations appear to have limited effects on trout in clear lakes, probably because trout are able to use deep littoral habitat and food supplies.

Seasonal effect on lactate dehydrogenase and citrate synthase in snapper ( Pagrus auratus) - S. A. Majed; R. M. G. Wells; B. H. Mcardle (New Zealand Journal of Marine and Freshwater Research, 2002)
The activities of two enzymes involved in metabolic energy production, lactate dehydrogenase (LDH) and citrate synthase (CS), were determined in the white trunk musculature of snapper, Pagrus auratus (Bloch & Schneider 1801), to determine whether the metabolic capacity reflects seasonal variations. LDH and CS activities for a population of wild fish were monitored on a monthly basis over a period of 1 year and correlated with body length and seasonal variation. Significant correlations were observed between enzyme activity and body length. Increased LDH activity may reflect energy demand for anaerobic burst swimming. In contrast, declining CS activity with increasing body length may indicate a reduction in energy generation. The seasonal variation of CS activity coincided with the somatic growth cycle, increasing from 1.18 U g −1 white muscle in winter to 1.79 in spring and 1.78 in late summer, whereas LDH activity did not show a clear seasonal pattern. This information could be useful for tracking metabolic capacity in field specimens using simple biochemical analysis.

Surface run‐off from mineralised road aggregate, Puhipuhi, Northland, New Zealand - D. Craw; D. Chappell; A. Black (New Zealand Journal of Marine and Freshwater Research, 2002)
Roads in the Puhipuhi area of Northland, New Zealand, have been surfaced with road aggregate derived from hydrothermally mineralised rocks, which contain iron sulphides (pyrite and marcasite). Oxidation of the iron sulphides results in localised acidification, typically to pH 3, on roads and in source quarries. This low pH is at least one pH unit more acidic than typical background pH of 4–5.5 in forested areas through which the roads pass. Regional background pH is near neutral, and this may be in part an anthropogenic result of development of farmland in the Puhipuhi area. Lower natural pH is partly because of variable degrees of mineralisation of the underlying rocks on the 100 m scale. Arsenic (As) is the best metallic indicator of mineralisation, and mineralised rocks commonly have As contents between 100 and 1000 ppm above a regional background of 5–20 ppm (fresh greywacke) and 0.2–5 ppm (basalt and clay‐altered greywacke). Road aggregates have As between 20 and 200 ppm, locally lower than naturally mineralised rocks and soils. Mineralised rocks have 1–100 ppm mercury (Hg) above regional background of 0.1–0.25 ppm (fresh greywacke) and 0.04 to 0.14 ppm (basalt and clay‐altered greywacke). Soils have up to 10‐fold variation in As and Hg within the soil profile, with high metal levels in the C horizon associated with iron oxyhydroxides. Base metals, copper (Cu), lead (Pb), and zinc (Zn) are generally near to regional background throughout the Puhipuhi area, including road aggregates. Neither As nor Hg are significantly mobilised in solution in run‐off from road aggregate, but the low pH signature of road run‐off can be traced for c. 50 m into forest soil, or more than 300 m in clay‐based watercourses. Sediments carried with the road run‐off may release As and Hg if they are transported into higher pH environments such as major rivers or farmland. The chemical effects of road run‐off are likely to be less than those from the natural mineralised rock occurrences that underlie many parts of the Puhipuhi area.

Demersal fish assemblages along the continental shelf and upper slope of the east coast of the South Island, New Zealand - Michael P. Beentjes; Brian Bull; Rosie J. Hurst; Neil W. Bagley (New Zealand Journal of Marine and Freshwater Research, 2002)
Data collected during five winter and three summer research trawl surveys in Pegasus Bay and Canterbury Bight (10–400 m), east coast of the South Island, New Zealand, were used to identify demersal fish assemblages from hierarchical cluster analysis and non‐metric multidimensional scaling. The environmental variables—depth, latitude, season, water temperature, sediment type, sea surface condition, and sea colour—were examined to determine their relationship to fish assemblages using multivariate redundancy analysis. Patterns of species richness were examined and described. Catch rates were generally higher in summer than winter (21 of 28 species) and higher in south Canterbury Bight in the depth range 30–200 m. Preferred depth was greater in winter than summer (21 of 28 species). Species richness declined with depth in winter. Four main demersal species assemblages were identified (inner shelf, outer shelf, shelf break, and upper slope) with minor changes in membership between summer and winter mostly as a result of a change in species preferred depth. Depth was the primary variable influencing fish assemblages with secondary effects of latitude, sediment, and bottom temperature.

Bob McDowall—his contribution to New Zealand's freshwater fish - Don Jellyman (New Zealand Journal of Marine and Freshwater Research, 2002)

Editorial board (New Zealand Journal of Marine and Freshwater Research, 2002)

Habitat preferences of giant kokopu, Galaxias argenteus - Martin L. Bonnett; Julian R. E. Sykes (New Zealand Journal of Marine and Freshwater Research, 2002)
The giant kokopu (Galaxias argenteus (Gmelin 1789)) is endemic to New Zealand, and is regarded as threatened. A perceived decline of the species has been attributed mostly to the loss and degradation of its habitat. To determine habitat requirements, information from the New Zealand Freshwater Fisheries Database, and from field surveys in the South Island were analysed. These indicated that five habitat features are important: in‐stream cover, deep water, low water velocity, proximity to the sea, and overhead shade/riparian cover. These features were important in two distinct regions surveyed and for both juvenile and adult fish. The effects of different types of riparian and in‐stream cover were examined, but it appeared that the presence of some form of cover was more important than its composition. The conservation and management of giant kokopu will probably continue to be based upon management of their habitat, and these processes will be enhanced by the knowledge of the species’ habitat requirements.

Growth, survival, and recruitment of juvenile shortfinned eels ( Anguilla australis) in a large New Zealand coastal lake - Eric Graynoth; Donald J. Jellyman (New Zealand Journal of Marine and Freshwater Research, 2002)
Annual changes in the size composition and relative abundance of juvenile shortfinned eels ( Anguilla australis Richardson) in Lake Ellesmere, New Zealand, were studied. Juveniles ( −1 (range 6.3–22.9 mm year −1 ), and are probably limited by the lack of food. Juvenile eels had high survival rates, exceeding 0.80 year −1 and were probably close to 1.0 year −1 . Recruitment into this shallow, turbid, brackish lake was variable and was correlated with the duration and timing of the lake's opening to the sea. The decline in growth rates and restricted recruitment in recent years could reduce commercial catches of migrating silver eels for the next 10–15 years.

Spatial and temporal variability in length of glass eels ( Anguilla spp.) in New Zealand - B. L. Chisnall; D. J. Jellyman; M. L. Bonnett; J. R. Sykes (New Zealand Journal of Marine and Freshwater Research, 2002)
The spatial and temporal trends in length and pigmentation of glass eels for the shortfinned eel (Anguilla australis (Richardson)) and the longfinned eel (A. dieffenbachii (Gray)), were investigated by electric‐fishing 13 New Zealand streams/rivers on both the east and west coasts, at 14‐day intervals between July and December, from 1995 to 1998. A total of 11 479 glass eels were individually identified, measured, and assigned a pigmentation stage. On the basis of pigmentation, 67% were described as “newly arrived”. Modal pigmentation stage advanced over the arrival season for both species, and on arrival, longfinned glass eels were usually more pigmented than shortfinned glass eels. For any given time, North Island glass eels were consistently more advanced in pigmentation than were their South Island counterparts. Few very early pigmentation stages were recorded from the North Island samples, probably because sample sites were above estuaries and harbours. Longfinned glass eels were generally longer than shortfinned glass eels from the same river. Length of both species declined during the arrival season. Regional differences in mean length provides some indication of arrival patterns—predominantly from the north in an anti‐clockwise dispersal around New Zealand. Recruitment also showed annual variation, which appeared to be influenced by the El Niño Southern Oscillation, with the arrival route appearing to be more strongly from the north‐west during the El Niño phase (persistent westerlies) and from the north‐east during the La Niño phase (more persistent north‐easterlies). The mean length of new arrivals increased in the north and in the south‐west between 1995 and 1997, and decreased in all regions between 1997 and 1998, which could have been the result of changes in the duration of migration. Possible reasons for this include spatial and temporal changes to spawning, and oceanic variations in production.